Analisis Kapabilitas Dan Model Manajemen Sumber Daya Manusia, Manajemen Ekonomi Dan Bisnis Dalam Produksi Keripik Rumput Laut Di Palembang - Irian Nasri; Januar Ida Wibowati; Nita Novianti (Journal of Innovative and Creativity, 2025)
So that the Palembang City seaweed chips industry can develop sustainably, this research emphasizes the need for an integrated strategy to improve the quality of human resources. To improve community welfare, especially in coastal villages, this study focuses on Griya Sako Palembang, the main location for producing seaweed chips. This study investigates the dynamics of local seaweed chips cultivation with an emphasis on natural conditions utilizing case study methodology and descriptive qualitative methodology. To provide a complete picture of seaweed production, data was collected through observation, interviews and documentation. The study's conclusions highlight enabling factors such as effective collaboration and adequate equipment as well as barriers such as unpredictable weather, inadequate water, and fluctuating costs. Although their reach is still limited, training programs organized by local governments have the ability to improve technical skills. To overcome these obstacles and encourage productivity and long-term economic growth in the seaweed chips industry in Palembang, this study emphasizes the need for capacity development and technical training